(untitled) (Journal of Emerging Technology in Teaching and Learning (JETTLe), 2026)
This study aims to develop a practical and effective game-based learning media to address the lack of teacher creativity in designing digital media, specifically for Javanese language subject on Wayang material at MI Tegalroso Parakan. This Research and Development (R&D) used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were third-grade students of MI Tegalroso Parakan (n=8). Data collection instruments included needs questionnaires, media and material expert validation sheets, and learning outcome tests (pre-test and post-test). Data were analyzed using descriptive and inferential statistics (Kolmogorov-Smirnov normality test, paired sample t-test, and N-Gain calculation). Expert validation results showed that the TEBANG game media was feasible to use with eligibility percentages of 85% (media expert) and 88% (material expert). The effectiveness test through paired sample t-test showed a significant difference between pre-test (Mean=73.63) and post-test (Mean=85.00) scores with sig. 0.025 (p < 0.05). The N-Gain score of 0.3671 proved the improvement of student learning outcomes in the medium category. This research develops a "Picture Guessing" game genre specifically for Wayang character introduction using the code-free Quick App Ninja platform. This represents a practical and realistic solution for teachers with limited programming competencies, while also functioning as a medium for preserving Javanese culture through an edutainment approach. The TEBANG media provides an innovative, easily accessible (web-based), and easily developed solution for MI/SD teachers. Its implementation is expected to improve learning outcomes, motivation, and active student participation in learning Javanese language and Wayang culture.